2011
DOI: 10.1021/ac103106y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Quadrupole Resonance: A Technique to Control Hydration Processes in the Pharmaceutical Industry

Abstract: Pharmaceuticals can exist in many solid forms, which can have different physical and chemical properties. These solid forms include polymorphs, solvates, amorphous, and hydrates. Particularly, hydration process can be quite common since pharmaceutical solids can be in contact with water during manufacturing process and can also be exposed to water during storage. In the present work, it is proved that NQR technique is capable of detecting different hydrated forms not only in the pure raw material but also in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…A similar investigation for the antidiabetic drug diabinese can be found in References [11]. In Reference [12] the authors show the clear distinguishability of differently hydrated species of diclofenac preparations and confirm the usefulness of NQRS for hydration monitoring of drug compounds containing quadrupolar nuclei. An application with high potential impact is the detection of explosives, as important compounds like Trinitrotoluene (TNT) and Cyclotrimethylenetrinitramine, commonly labelled as RDX, have very characteristic NQR fingerprints, see, for example, References [13,14].…”
Section: Introductionsupporting
confidence: 57%
“…A similar investigation for the antidiabetic drug diabinese can be found in References [11]. In Reference [12] the authors show the clear distinguishability of differently hydrated species of diclofenac preparations and confirm the usefulness of NQRS for hydration monitoring of drug compounds containing quadrupolar nuclei. An application with high potential impact is the detection of explosives, as important compounds like Trinitrotoluene (TNT) and Cyclotrimethylenetrinitramine, commonly labelled as RDX, have very characteristic NQR fingerprints, see, for example, References [13,14].…”
Section: Introductionsupporting
confidence: 57%
“…In a recent publication, Limandri et al demonstrated that nuclear quadrupole resonance (NQR) spectroscopy is also a useful tool to identify hydrates and also monitor hydration dynamics. NQR is otherwise known to be able to identify and quantify different polymorphs in pharmaceutical agents. The NQR spectrum is typically simple, i.e.…”
mentioning
confidence: 99%
“…surroundings for the α-and β-polymorphs via the spin-lattice relaxation time, , measurements is additional information. It is a valuable supplement to the 13 C and 15 N NMR magic angle spinning data (chemical shifts) as well as the corresponding data for all three polymorphs [40]. Article [25] concludes with " 14 N NQR studies demonstrate that we were dealing with the room temperature stable forms of all three polymorphs.…”
Section: N Nqr In Sulfanilamidementioning
confidence: 99%
“…The view into the lattice dynamics of the N(1) and N(2) nitrogen atoms and their surroundings for the αand β-polymorphs via the spin-lattice relaxation time, T 1 , measurements is additional information. It is a valuable supplement to the 13 C and 15 N NMR magic angle spinning data (chemical shifts) as well as the corresponding T 1 data for all three polymorphs [40].…”
Section: N Nqr In Sulfanilamidementioning
confidence: 99%
See 1 more Smart Citation